2011
DOI: 10.1007/s00018-011-0817-0
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamus and the neurobiology of drug seeking

Abstract: The hypothalamus is a neural structure critical for expression of motivated behaviours that ensure survival of the individual and the species. It is a heterogeneous structure, generally recognised to have four distinct regions in the rostrocaudal axis (preoptic, supraoptic, tuberal and mammillary). The tuberal hypothalamus in particular has been implicated in the neural control of appetitive motivation, including feeding and drug seeking. Here we review the role of the tuberal hypothalamus in appetitive motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 145 publications
4
42
0
Order By: Relevance
“…McNally and colleagues continued their investigation of the role of sub-regions of hypothalamus and thalamus and their projections in context-induced reinstatement of alcoholic beer seeking in the drug (A) context, as well as extinction of alcohol seeking in the non-drug (B) context (Marchant et al 2012; Millan et al 2011). …”
Section: Recent Neurobiological Findingsmentioning
confidence: 99%
“…McNally and colleagues continued their investigation of the role of sub-regions of hypothalamus and thalamus and their projections in context-induced reinstatement of alcoholic beer seeking in the drug (A) context, as well as extinction of alcohol seeking in the non-drug (B) context (Marchant et al 2012; Millan et al 2011). …”
Section: Recent Neurobiological Findingsmentioning
confidence: 99%
“…Numerous reports have since shown that seeking for all major addictive drugs involves orexin neurons 36 . Reminiscent of their role in food seeking, orexins are preferentially involved in highly motivated drug seeking (for example, under progressive ratio reinforcement schedules or seeking that is triggered by salient external stimuli such as drug-paired cues or stressors) 30,36,39,4143 . Acute drug withdrawal also involves orexins, leading some to speculate that orexin neuron activity during withdrawal facilitates drug seeking to alleviate this specific ‘drug need state’ 42 .…”
Section: The Many Faces Of Orexin/hypocretin Functionmentioning
confidence: 99%
“…The first time drugs of abuse are used (e.g., psychostimulants, alcohol, opioids, nicotine, Δ 9 tetrahydro-cannabinol), brain regions in both reward (i.e., ventral tegmental area, striatum, nucleus accumbens core, thalamus) and learning (basolateral and central nucleus of the amygdala, medial prefrontal cortex, hippocampus) centers share excitatory information (reviewed in Koob & Volkow 2010; Marchant et al, 2012). Some of these structures serve a primary role in particular stages of addiction (e.g., binge/intoxication, withdrawal/negative affect, and preoccupation/anticipation/craving; Koob & Volkow, 2010) and memory processes (i.e., encoding, consolidation, and retrieval; e.g., Bernardi et al, 2009; Lalumiere et al, 2012), yet many of these regions can be recruited throughout each process.…”
Section: Learning Processes Involved In the Development Of Addictionmentioning
confidence: 99%